Recent advances in corpus linguistics: developing and exploiting corpora - Vandelanotte, Lieven; Davidse, Kristin; Gentens, Caroline; Kimps, Ditte (Language and computers, 2014)
This book is a selection of studies presented at the 33rd International Conference of the International Computer Archive of Modern and Medieval English (ICAME), hosted by the University of Leuven (30 May - 3 June 2012). The strictly refereed and extensively revised contributions collected here represent recent advances in corpus linguistics, both in the development of specialist corpora and in ways of exploiting them for specific purposes. The first part focuses on "Corpus development and corpus interrogation" and features papers on the compilation of new, highly specialized corpora which aim to fill gaps in historical databases, and on new ways of extracting relevant patterns automatically from computerized datasets. The second part, devoted to "Specialist corpora", presents detailed descriptive studies on grammatical patterns in World Englishes, on neology, and - using a contrastive approach - on prepositions and cohesive conjunctions. The third and final part on "Second language acquisition" groups together studies situated at the intersection of corpus linguistics and educational linguistics and dealing with markers of relevance and lesser relevance in lectures, deceptive cognates, the automatic annotation of native and non-native uses of demonstrative this and that, and measuring learners' progress in speech and in writing. Each contribution in its own way reports on novel ways of getting mileage out of specialist corpora, and collectively the contributions attest to the rude health of computerized corpus linguistic studies
Keywords: Konferenzschrift -- 2012 -- Löwen; Korpus; Englisch